2019
DOI: 10.1002/srin.201900265
|View full text |Cite
|
Sign up to set email alerts
|

Hot Ductility and Fracture Phenomena of Low‐Carbon V–N–Cr Microalloyed Steels

Abstract: The hot ductility of low‐carbon V–N–Cr microalloyed steel is studied using a thermomechanical simulator. The steel is solution treated at 1350 °C and cooled at 15 °C s−1 to the test temperature in the range of 650–1200 °C. Next, they are strained to failure at a strain rate of 4 × 10−3 or 4 × 10−2 s−1, and ductility troughs are obtained. The results reveal a ductility trough in V–N–Cr steels in the range of 650–900 °C with a minimum reduction in area (RA) value of 13.5 % at 800 °C and strain rate of 4 × 10−3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Thus, when RA = 60%, the temperature is used to define the plastic zone and brittleness. [ 3 ] The variation of RA of steel at different strain rates in the temperature range from 650 to 1100 °C is shown in Figure 4 and Table 2 . It can be seen from Figure 4 that the ductility troughs were found in the temperature range of 650–1100 °C at strain rates of 1.0 × 10 −3 , 5.0 × 10 −3 , and 1.0 × 10 −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when RA = 60%, the temperature is used to define the plastic zone and brittleness. [ 3 ] The variation of RA of steel at different strain rates in the temperature range from 650 to 1100 °C is shown in Figure 4 and Table 2 . It can be seen from Figure 4 that the ductility troughs were found in the temperature range of 650–1100 °C at strain rates of 1.0 × 10 −3 , 5.0 × 10 −3 , and 1.0 × 10 −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 1,2 ] However, if excessive microalloying elements are added, a significant number of large‐size precipitates are precipitated at the grain boundaries, which reduce the plasticity of steel and promote a significant increase in surface cracks in continuously cast billets. [ 3–5 ] The surface cracks of the cast slab are mainly divided into transverse crack and longitudinal crack. Surface cracks are stress concentrators that can lead to the formation of different types of surface defects on products.…”
Section: Introductionmentioning
confidence: 99%
“…medium/high carbon steels). 17,22,28) On top of this, the peritectic transformation leads to significant volume changes leading to internal stresses which may result in further cracking of the final product.…”
Section: Identification Of Cracking Issues and Process Improvements Tmentioning
confidence: 99%
“…31,32) It has been demonstrated that Nb has a strong detrimental effect when its content ranges between 0,03-0,04 wt.%Nb, which could promote cracking due to carbo-nitrides precipitation associated with low ductility. 22,28,[33][34][35][36] Yet, Nb is still used due to its beneficial effects on final mechanical properties. A possible way to circumvent this issue is to combine Nb with V and Ti which have a lesser effect on ductility loss.…”
Section: Identification Of Cracking Issues and Process Improvements Tmentioning
confidence: 99%
“…Alloy steels containing Ti, Nb, and V have a wide distribution of trough with poor ductility. [1][2][3] Thus, it makes difficult to minimize surface cracking. When cracking is generated on the surface of cast steel, surface treatment methods, such as scraping or grinding, are required.…”
Section: Introductionmentioning
confidence: 99%